Vulnerable to verdant: turning flood risk into farm resource - Signs, M. (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Increasing production in agriculture is often a very long and arduous process. Agronomists, soil scientists and hydrologists who implement land and water interventions are lucky if they see a 15% increase in yield after years of working on a specific site. But what if you were able to achieve a more than 500% increase in just three years, specifically in an area where there had been virtually no crop production in the past, all while making pastoralist more resilient to climatic changes and reducing the risk of water related disasters?https://wle.cgiar.org/thrive/2019/05/26/vulnerable-verdant-turning-flood-risk-farm-resource